Enhancing distance learning in Makato, Aklan through information and communication technology a prototype for the REAP program - Vargas, Flora Molina (2006)
Distance or Open or Online learning has become a reputable system of education as it uses the new technology. This has become a recourse for those who afford to pay but cannot attend regular classes in the four walls of an educational institution. Many out-of-school youth and adults are in situations where they cannot avail of regular classroom education. Their main reason is poverty. They have to help the family earn a living or take care of the children. It is for this people that the Re-Entry Education Alternative for the Poor Program was established by Angelicum College in 1999.Through the REAP program Angelicum College offers free education to the out of school youth and adults by providing them printed self-learning materials or Modules. The REAP learners are limited to the printed modules which have originally been designed for the regular Angelicum students in Quezon City, who avail of other learning resources and technology.It is for this reason that I have undertaken this study-- to know how information and communication technology (ICT) can be used to enhance the distance learning of REAP learners and how communication between the teachers/tutors and the learners can be facilitated to improve the distance learning process. The study described the REAP learners in Makato, Aklan; identified the factors that determine their use of media and the different forms of media that they use. It also determined the media appropriate for the enhancement of learning of the REAP learners and the communication relationship between the learners, teachers and the volunteer coordinator and tutors. It also pointed out how communication between the teachers and the learners can be facilitated to improve the distance learning process. The study was based on theories of communication and distance learning namely Technological Determinism (1962), System theory (1978), Constructivism (1987), the Theory of Interaction and Communication (1986), Theory of Independent Study (1971 & 1981). The Volunteer Management Theory was also employed in this study. The data were gathered using methodological triangulation--survey, case study and focus group discussions. The research concluded that the learners need to be helped in English, understanding the lessons and becoming proactive learners.ICT can be used as substitutes for the teachers, as motivators for study and for improving the pace of the learning. The research emphasized the role of the community in facilitating communication and the distance learning process. Based on the conclusions, a prototype program was produced to encourage the future production of learning materials using ICT. If enhanced with the ICT, the REAP Program will better contribute to making the dream of education for all a reality.